Socio-Historical Dynamics of Islamic Education in the Indonesian Archipelago: The Institutional Evolution of Pesantren and Madrasah - Syed Ahmad Ali Shah; Ali Rohmad; Ashimatul Alai (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2026)
The historical development of Islamic education in the Indonesian archipelago reflects a dynamic process of institutional transformation shaped by socio-cultural, religious, and political changes. Despite numerous studies on pesantren and madrasah, limited attention has been given to examining their evolution within a comprehensive socio-historical framework. This study aims to analyze the evolution of Islamic educational institutions in the archipelago, focusing specifically on the historical development and institutional transformation of pesantren and madrasah in Indonesia. This research employs a qualitative method based on a literature review. Data were collected from various scholarly sources, including books, academic journals, historical documents, and relevant articles. The collected data were analyzed descriptively to trace patterns of continuity and change in Islamic educational institutions over time. The findings reveal that Islamic education in the archipelago evolved gradually from informal religious instruction conducted in homes and mosques to more structured institutions such as pesantren, dayah, surau, meunasah, and later madrasah. Pesantren emerged as early centers of Islamic learning characterized by non-classical systems centered on Kiai, students (santri), dormitories, and religious texts. The establishment of madrasah marked a significant phase of modernization by introducing a more formal and systematic educational structure without displacing pesantren. Instead, both institutions developed in complementary ways and played a crucial role in strengthening Islamic education in Indonesia. This research suggests that understanding the historical continuity and adaptability of these institutions is essential to developing responsive, contextually grounded Islamic education policies in contemporary Indonesia.